Content analysis of the theory of progress in Ayatollah Khamenei's thought and its boundaries with theories of development - sayed ahmad hosaini; sayyed majid motahari nejad; sayyed hosain hosaini (Religion & Communication, 2023)
Today, development has become one of the main goals and aspirations of human societies, which has influenced most of the policies, structures and programs of different countries. On the other hand, the crisis of meaning in developed societies and the crisis of structure in underdeveloped societies are serious and complex issues that have led to imbalances in the continuum of development. While developed countries in terms of cultural relations and internal identity are in the circle of group interests and beyond in terms of external relations with different human societies are in the circle of national interests regardless of the conditions and needs of other countries. And they are pumping the crisis of meaning into all human societies, the underdeveloped and developing countries are constantly changing all their social structures to be thrown to a level beyond development, and in the maze of theories, They get caught up in their own development patterns and plans. In this regard, the present article examines the various schools of development in the world and then, by presenting the foundations of progress in the thought of the Supreme Leader of the Islamic Revolution of Iran, Ayatollah Khamenei, tries to compare the components of this new school with existing schools in the world. Therefore, relying on the library method, common patterns of development in the West along with emerging models of development, as well as the principles and components of development in the intellectual system of Muslim thinkers and revolutionary leaders of Ayatollah Khamenei have been extracted and In order to explain and extract the network of themes of the principles of progress in the mental geometry of the Supreme Leader of the Revolution, his statements and writings in two areas of principles and pragmatic strategies of progress have been analyzed by content analysis and finally compared with other schools of development in a comparative study table. Ayatollah Khamenei's school of progress in general has six central components: Sharia-based and excellence-oriented, efficient and dignity-oriented social relations: in the field of justice, health, communication, etc., based on the presence of the nation-state, indigenous, The idea of ​​the foundation has cultural-economic foundations.